2000
DOI: 10.1016/s0006-3495(00)76832-9
|View full text |Cite
|
Sign up to set email alerts
|

GOLAC: An Endogenous Anion Channel of the Golgi Complex

Abstract: The Golgi complex is present in every eukaryotic cell and functions in posttranslational modifications and sorting of proteins and lipids to post-Golgi destinations. Both functions require an acidic lumenal pH and transport of substrates into and by-products out of the Golgi lumen. Endogenous ion channels are expected to be important for these features, but none has been described. Ion channels from an enriched Golgi fraction cleared of transiting proteins were incorporated into planar lipid bilayers. Eighty p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 50 publications
3
27
0
Order By: Relevance
“…In this circumstance, it is likely that eliminating CFTR has no effect on pH G , because other K ϩ and Cl Ϫ channels can provide sufficient counterion conductance to ensure that membrane potential in the Golgi is small and therefore has little effect on H ϩ pumps or leaks. Two other studies have provided evidence for the presence of Cl Ϫ channels in the Golgi: Nordeen et al (35) found an anion channel in enriched Golgi fractions, and Schwappach et al (46) found that Gef1p (the only yeast ClC Cl Ϫ channel) localizes to the Golgi. Additionally, elimination of Gef1p from yeast does result in altered cation homeostasis (17) but does not effect Kar2p secretion or glycosylation of invertase, both dependent on an acidic Golgi (46).…”
Section: Cftr Counterion Conductance and Membrane Potential In Detementioning
confidence: 99%
“…In this circumstance, it is likely that eliminating CFTR has no effect on pH G , because other K ϩ and Cl Ϫ channels can provide sufficient counterion conductance to ensure that membrane potential in the Golgi is small and therefore has little effect on H ϩ pumps or leaks. Two other studies have provided evidence for the presence of Cl Ϫ channels in the Golgi: Nordeen et al (35) found an anion channel in enriched Golgi fractions, and Schwappach et al (46) found that Gef1p (the only yeast ClC Cl Ϫ channel) localizes to the Golgi. Additionally, elimination of Gef1p from yeast does result in altered cation homeostasis (17) but does not effect Kar2p secretion or glycosylation of invertase, both dependent on an acidic Golgi (46).…”
Section: Cftr Counterion Conductance and Membrane Potential In Detementioning
confidence: 99%
“…Eukaryotic cells contain functional channels in the endoplasmic reticulum and sarcoplasmic reticulum [1][2][3] ; specific ion channels have also been identified in the inner nuclear membrane [4], mitochondrial membranes [5,6], Golgi membranes [7,8] and secretory vesicles [9][10][11]. Some of these channels are involved in the mobilization of intracellular Ca# + [1,2] and the transport of metabolites [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, for many Cl Ϫ channels, it has not been possible to associate molecular identity with function (19). In hepatocytes, as yet unidentified Cl Ϫ channels participate in cell volume regulation (1,7,22,23) and acidification of intracellular organelles (5,24,28,36). The ClC Cl Ϫ channel family has proven to be important in diverse cellular functions (10,14,40).…”
mentioning
confidence: 99%